MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK TERHADAP BERITA KORUPSI BERBASIS MEDIA INFOGRAFIS CANVA DALAM PEMBELAJARAN IPS (Penelitian Tindakan Kelas Pada Kelas VIII-B SMP Kartika XIX-2 Bandung) - Hana Listia Lugina, - (2020)
This research is aimed to handle the main problem; it is students are having poor critical thinking in learning social sciences. Students are having poor interest in reading various information sources because of that problem, either digital or conventional, students are having poor ability in sorting valid information source, students are having poor analytic ability in relating various surrounding problems with the values of learning social sciences, students' ability in using technology as learning media in order to develop critical thinking ability are poor, students are having poor interest in examine various corruption problems, students also are having poor ability in propound an idea based on critical thinking framework. Therefore, it needs learning innovation which could improve students' critical thinking ability. By using corruption news and canva info graphic, students are asked to search and analyze various informations which related to the value of learning social sciences which is relevant with its corruption news. Classroom action research method which is used in this research is Kemmis and Taggart model with three cycles. Observation, interview and documentation study were done to collect the data. The research subject is 32 students of class VIII B SMP Kartika XIX-2 Bandung in social sciences subject. The use of corruption news and canva info graphic shows the difference of students' critical thinking ability in learning social sciences. The conclusion came from the asessesment of students'critical thinking in knowledge level. at the first cycle the average scores were "C" or enough. At the second cycle, the scored increased into "SB" or excellent. And the third cycle the scores were "SB" or excellent. In the assesment of product, the first cycle the average scores are "B" or good. At the second cycle, the scored increased into "SB" or excellent. And the third cycle the scores were "SB" or excellent. According to the result of this study can be concluded that the usage of corruption news with canva infograpics could improve students' critical thinking ability in learning social science subject. Keywords: corruption news, canva infographic, critical thinking, social sciences learning